Review On Ayurvedic And Modern Concept Of Mutravridhi - Meena, Deepshikha; Gupta, Rajesh Kumar (International Research Journal of Ayurveda & Yoga, 2021)
Mutravridhi is one of the most common type of Vridhi roga.It is also known as vrishan vridhi. Accumulation of mootra in vrishana is main cause of vrishan vridhi. Vridhi means pathological accumulation of dosh and dhatu, but mutravridhi is mainly due to increase vata dosha .Acharyas mentioned shastra karma for management of mutravriddhi. Mutravridhi can be compared to hydrocele. Swelling in the scrotum is collection of water like fluid between the two layers of tunica vaginalis membrane of testis causing hydrocele. It may be congenital or acquired or associated with certain severe underlying diseases. It is more common in infant but can also occur at any age later in life. Painless scrotal swelling is more commonly seen in hydrocele. In management of mild hydroceles bed rest and scrotal support is generally recommended. In severe condition surgical drainage required. The treatment of choice in hydrocele is surgical intervention.